'For a mere cough, men must just chew Conjex, gain strength, and continue working': the provider construction and tuberculosis care-seeking implications in Blantyre, Malawi - Jeremiah Chikovore; Graham Hart; Moses Kumwenda; Geoffrey A. Chipungu; Liz Corbett (Taylor & Francis Group, 2015)
Background: Delay by men in seeking healthcare results in their higher mortality while on HIV or tuberculosis (TB) treatment and contributes to ongoing community-level disease transmission before going on treatment. Objective: To understand masculinity's role in delay in healthcare seeking for men, with a focus on TB-suggestive symptoms. Design: Data were collected between March 2011 and March 2012 in low-income suburbs in urban Blantyre using focus group discussions with community members (n=8) and health workers (n=2), in-depth interviews with 20 TB patients (female=14) and 20 uninvestigated chronic coughers (female=8), and a 3-day participatory workshop with 27 health stakeholder representatives. The research process drew to a large extent on grounded theory principles in the manner of Strauss and Corbin (1998) and also Charmaz (1995). Results: Role descriptions by both men and women in the study universally assigned men as primary material providers for their immediate family, that is, the ones earning and bringing livelihood and additional material needs. In a context where collectivism was valued, men were also expected to lead the provision of support to wider kin. Successful role enactment was considered key to achieving recognition as an adequate man; at the same time, job scarcity and insecurity, and low earnings gravely impeded men. Pressures to generate continuing income then meant constantly looking for jobs, or working continuously to retain insecure jobs or to raise money through self-employment. All this led men to relegate their health considerations. Conclusions: Early engagement with formal healthcare is critical to dealing with TB and HIV. However, role constructions as portrayed for men in this study, along with the opportunity costs of acknowledging illness seem, in conditions of vulnerability, important barriers to care-seeking. There is a need to address hidden care-seeking costs and to consider more complex interventions, including reducing precarity, in efforts to improve men's engagement with their health.